2012
DOI: 10.5194/acp-12-9763-2012
|View full text |Cite
|
Sign up to set email alerts
|

Observations of atmosphere-biosphere exchange of total and speciated peroxynitrates: nitrogen fluxes and biogenic sources of peroxynitrates

Abstract: Abstract.Peroxynitrates are responsible for global scale transport of reactive nitrogen. Recent laboratory observations suggest that they may also play an important role in delivery of nutrients to plant canopies. We measured eddy covariance fluxes of total peroxynitrates ( PNs) and three individual peroxynitrates (APNs ≡ PAN + PPN + MPAN) over a ponderosa pine forest during the Biosphere Effects on AeRosols and Photochemistry EXperiment 2009 (BEARPEX 2009). Concentrations of these species were also measured a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…A number of studies have reported fluxes of PAN using Eddy correlation and the ICIMS technique (Turnipseed et al, 2006;Wolfe et al, 2009;Min et al, 2012). Turnipseed et al (2006), in a study of PAN fluxes above loblolly pine, found that their measured deposition velocities were larger than were predicted by models and that PAN deposition velocities were increased in wet conditions, consistent with possible contamination of the PAN flux by PAA sensitivity.…”
Section: Implications For the Measurement Of Speciated Pan Fluxes By mentioning
confidence: 83%
See 2 more Smart Citations
“…A number of studies have reported fluxes of PAN using Eddy correlation and the ICIMS technique (Turnipseed et al, 2006;Wolfe et al, 2009;Min et al, 2012). Turnipseed et al (2006), in a study of PAN fluxes above loblolly pine, found that their measured deposition velocities were larger than were predicted by models and that PAN deposition velocities were increased in wet conditions, consistent with possible contamination of the PAN flux by PAA sensitivity.…”
Section: Implications For the Measurement Of Speciated Pan Fluxes By mentioning
confidence: 83%
“…They include a plot of the diurnal average of the NOaddition generated background signal and show a average diurnal cycle with a peak of 50 pptv PAN equivalent which is qualitively similar to the one reported in this paper observed in the afternoon indicating that the BEARPEX 2009 ICIMS was sensitive to PAA. Min et al (2012) estimate that PAA could be responsible for 10-40 % of the discrepancy between the different methods of estimating fluxes of PANs although they note that the PAN-equivalent data exhibits the opposite vertical gradient one would expect for a species with a faster deposition velocity. It is also possible that the tentative evidence that we obtained for peracid analogous to MPAN and PPN could be responsible for an addition small part of this discrepancy.…”
Section: Implications For the Measurement Of Speciated Pan Fluxes By mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of OH with methacryloyl peroxy nitrate (MPAN) is rapid, but MPAN is typically a minor component of total peroxy nitrates . The deposition rate of peroxy nitrates was not measured during SOAS, but previous measurements in a ponderosa pine forest estimate the deposition velocity to be between 0.5 and 1.3 cm s −1 (Wolfe et al, 2009;Min et al, 2012). Using this range of deposition velocities gives a total deposition loss rate of peroxy nitrates of 5 ± 3 ppt h −1 in the afternoon.…”
Section: Peroxy Nitratesmentioning
confidence: 99%
“…Sparks et al (2008) report a much higher dry NO y deposition contribution to total nitrate on an annual basis of around 60 % above a North Carolina pine plantation. Other studies using eddy covariance have applied novel instruments to directly determine the contribution of individual species over short-term (several months or less) intensive field campaigns at a number of sites across North America (Horii et al, 2004;Turnipseed et al, 2006;Farmer and Cohen, 2008;Wolfe et al, 2009;Min et al, 2012;Zhang et al, 2012). Gradient methods above forest canopies have also been used to determine the contributions of certain species to NO y deposition or emission budgets (Sievering et al, 2001;Pryor et al, 2002;Neirynck et al, 2007;Wolff et al, 2010).…”
Section: Total Deposition Budget Of Reactive Nitrogen Oxidesmentioning
confidence: 99%